DAMPAK PENGEMBANGAN USAHA INDUSTRI KECIL MENENGAH SEBAGAI SALAH SATU PROGRAM PEMERINTAH DAERAH KOTA BUKITTINGGI (STUDI KASUS: INDUSTRI KERUPUK SANJAI) - sarah, May; Ridha, Habibatur (Jurnal Ekonomi Sakti, 2024)
The purpose of this writing is to find out how regional government programs help Small and Medium Industrial businesses and the impact of government programs on the development of the Small and Medium Industry of Sanjai Crackers in Bukittinggi City. The analytical method used in this research is a qualitative method with a descriptive approach technique. This research shows that the small and medium industry of sanjai crackers in Bukittinggi City, in running its business as workers and business actors, requires assistance/guidance from the government to assist them in terms of processing methods, income assistance and product marketing. From the results of observations made, the government has not been able to provide guidance/assistance evenly to Small and Medium Industry (IKM) business actors in Bukittinggi City. Therefore, it is important for local governments to provide training and guidance equally to SMEs so that this sector can develop and become a source of pride for the City of Bukittinggi and West Sumatra Province.